Parapharyngeal chordoma: A diagnostic challenge and potential mimic of pleomorphic adenoma on fine‐needle aspiration cytology. Issue 1 (18th November 2011) - Castro, Michael; Aslan, Deniz; Manivel, J. Carlos; Pambuccian, Stefan E.; Michael, Claire W.
Abstract Chordomas are rare tumors that are usually located in the sacrococcygeal and sphenooccipital region. Their cytologic diagnosis is rather straightforward when sampled by fine‐needle aspiration (FNA) from these characteristic locations, especially when physalipherous cells are present. However, chordomas may pose difficult diagnostic challenges when encountered in unusual locations, such as the parapharyngeal region. We report the cytologic findings of a recurrent chordoma sampled through transoral FNA from the parapharyngeal space of a 66‐year‐old woman. As the prior history of chordoma was not available during the rapid onsite evaluation, the presence of bland epithelioid nonvacuolated cells and spindle cells intimately admixed with a fibrillary, intensely metachromatic material led to an initial diagnosis of pleomorphic adenoma. Review of the patient's prior pathology specimen and of the Papanicolaou‐stained smears and cellblock sections showing rare multivacuolated (physalipherous) cells led to the correct diagnosis, which was supported by immunoperoxidase stains (cytokeratin AE1/AE3+, S100+, GFAP−). A review of the literature found no previous instances in which chordomas mimicked pleomorphic adenoma on FNA. However, since the two tumors show significant cytomorphologic overlap, including the presence of abundant fibrillary matrix with embedded neoplastic cells and single bland spindle and epithelioid tumor cells with occasional intranuclear pseudoinclusions, we compared their cytologic features. A review of the FNA cytologic features of this case of chordoma and of 17 consecutive cases of pleomorphic adenoma found that the presence of a more abundant, focally vacuolated cytoplasm favors chordoma over pleomorphic adenoma. Diagn. Cytopathol. 2013. © 2011 Wiley Periodicals, Inc.